Protein-Based Nanohydrogels for Bioactive Delivery - Chander, Subhash; Kulkarni, Giriraj T.; Dhiman, Neerupma; Kharkwal, Harsha (Frontiers in Chemistry, 2021)
Hydrogels possess a unique three-dimensional, cross linked network of polymers capable of absorbing large amounts of water and biological fluids without dissolving. Nanohydrogels (NGs) or nanogels are composed of diverse types of polymers of synthetic or natural origin. Their combination is bounded by the chemical covalent bond or is physically cross-linked with non-covalent bonds like electrostatic interactions, hydrophobic interactions and hydrogen bonding. Its remarkable ability to absorb water or other fluids is mainly attributed to hydrophilic groups like hydroxyl, amide, sulphate etc. Natural biomolecules such as proteins or peptides based nanohydrogel is an important category of hydrogels which possess high biocompatibility and metabolic degradability. The preparation of protein nanohydrogels and subsequent encapsulation process generally involve use of environment friendly solvents and can be generated using different proteins, such as fibroins, albumin, collagen, elastin, gelatin, lipoprotein etc involving emulsion, electrospray, desolvation methods to name a few. Nanohydrogels are excellent biomaterial having broad applications in the areas of regenerative medicine, tissue engineering, and drug delivery due to certain advantages like biodegradability, biocompatibility, tunable mechanical strength, molecular binding abilities and customisable responses to certain stimuli like ionic concentration, pH and temperature. The present review aims to provide an insightful analysis of proteins/ peptide nano-hydrogels including their preparation, biophysiochemical aspects and applications in diverse disciplines like in drug delivery, immunotherapy, intracellular delivery, nutraceutical delivery, cell adhesion, and wound dressing. Naturally occurring structural proteins being explored in protein nanohydrogels along with their unique properties are also discussed briefly. Further, the review also covers the advantages, limitations, overview of clinical potential, toxicity aspects, stability issues and future perspectives of protein nanohydrogel.